Isolation of Karanjin from Pongamia Pinnata and Its Identification by Difference Analytical Techniques - Kumar Dhanmane, Sushil; A. Salih, Faisal (Kurdistan Journal of Applied Research, 2018)
Karanjin is the medicinal drug that used as anti- inflammatory and anti-cancer. The object of this study is to isolate karanjin in karanja (pongamia pinnata Linn.) seed oil. The seed oil was subjected to triple petroleum with continuously constant shaking for first 48 hours, 24 hours for each second and third extraction then separated under reduced pressure at 50?C on rotatory evaporate to get yellow viscous oil. Separate non-fatty components using ethanol solvent and reduced under 50?C with pressure to get (43.33 g) yellow oil. The oil was kept for 3 days at 45?C in refrigerator white deposited at bottom of oil, the residue recrystallized with methanol it should be done fast and carefully to prevent solubility of karanjin in methanol partially, the purity of isolated karanjin was found to be (99.623%). From TLC, HPL, IR, 1HNMR, 13CNMR spectra data, structure elucidation was done and the structure was confirmed as karanjin.